377. High Resistance and Mortality Rates in Patients With Ventricular Assist Device (VAD)-Associated Candidemia: A Need for Alternative Antifungal Strategies. (26th November 2018) - Fong, Gary; Beyda, Nicholas D
Abstract: Background: VADs are increasingly utilized in the management of end-stage heart disease. Infections are frequently encountered in VAD patients, are difficult to manage, and delay heart transplant. Prior studies have illustrated that fungal infections are rarer than bacterial infections but carry a higher mortality rate. Published data regarding the treatment and outcomes of fungal infections in VAD patients are scarceThe objective of this study was to describetreatment patterns, clinical outcomes and antifungal resistance rates in this unique patient population. Methods: This was a retrospective cohort study that included VAD patients 18 years and older admitted to Baylor St. Luke's Medical Center in Houston, Texas between 2009 and 2016 with a positive blood culture for Candida spp. Patients with more than one Candida spp. isolated were excluded. Patient data were collected using electronic medical records and microbiology laboratory reports. Results: Out of 835 VAD patients screened, there were 57 candidemia episodes across 38 patients resulting in an incidence of 6.2%. C. glabrata was the most common species (13/38, 34.2%), followed by C. albicans (10/38, 26.3%), C. parapsilosis (6/38, 15.8), C. tropicalis (5/38, 13.2%), and C. krusei (3/38 (7.9%). Ten patients had an echinocandin nonsusceptible first isolate (26.3%). In patients with recurrent candidemia, echinocandin nonsusceptibility rose as high as 55.6%. Candida species was the only independent risk factor for antifungal nonsusceptibility (OR, 1.9; 95% CI, 1.0–3.4). Micafungin was the most common initial antifungal (34/38, 89.5%) but seven patients required salvage therapy with amphotericin and/or combination therapy (18.4%). Nineteen patients died prior to discharge (50.0%) and 29 patients died within 1 year (76.3%). Independent risk factors for in hospital mortality included APACHE II score (OR, 1.4; 95% CI, 1.1 – 1.8) and persistent candidemia (OR, 12.9; 95% CI, 1.3–129.6). Only three patients survived to heart transplant (7.9%). Conclusion: Resistance and mortality rates in this patient population are extremely high. Micafungin was the most common antifungal used but antifungal choice did not appear to impact 1 year mortality. While this is the largest cohort of patients with VAD-associated candidemia to date, larger, prospective studies are needed to guide management of these infections. Disclosures: N. D. Beyda, Astellas: Grant Investigator and Scientific Advisor, Consulting fee and Research grant.